Higher intake of fish and fat is associated with lower plasma s-adenosylhomocysteine: a cross-sectional study - Vendelbo Lind, Mads; Lauritzen, Lotte; Pedersen, Oluf; Vestergaard, Henrik; Stark, Ken; Hansen, Torben; Ross, Alastair B.; Kristensen, Mette (Elsevier, 2017)
Several B-vitamins act as co-factors in one-carbon metabolism, a pathway that plays a central role in several chronic diseases. However, there is a lack of knowledge of how diet affects markers in one-carbon metabolism. The aim of this study was to explore dietary patterns and components associated with one-carbon metabolites. We hypothesized that intake of whole-grains and fish would be associated with lower Hcy, and higher SAM:SAH ratio due to their nutrient content. We assessed dietary information using a four-day dietary record in 118 men and women with features of the metabolic syndrome. In addition we assessed whole-blood fatty acid composition and plasma alkylresorcinols. Plasma s-adenosylmethionine (SAM), s-adenosylhomocysteine (SAH), homocysteine (Hcy) and vitamin B12 was included as one-carbon metabolism markers. We used principal component analysis (PCA) to explore dietary patterns and multiple linear regression models to examine associations between dietary factors and one-carbon metabolites. PCA separated subjects based on prudent and unhealthy dietary patterns, but the dietary pattern score was not related to the one-carbon metabolites. Whole grain intake was found to be inversely associated to plasma Hcy (?4.7% (?9.3; 0.0), P=.05) and total grain intake tended to be positively associated with SAM and SAH (2.4% (?0.5; 5.5), P=.08; 5.8% (?0.2; 12.1), P=.06, respectively, per SD increase in cereal intake). Fish intake was inversely associated with plasma Hcy and SAH concentrations (?5.4% (?9.7; ?0.8), P=.02 and ?7.0% (?12.1; ?1.5), P=.01, respectively) and positively associated with the SAM:SAH ratio (6.2% (1.6; 11.0), P=.008). In conclusion, intake and fish and whole-grain appear to be associated with a beneficial one-carbon metabolism profile. This indicates that dietary components could play a role in regulation of one-carbon metabolism with a potential impact on disease prevention.
The final publication is available at Elsevier via https://doi.org/10.1016/j.nutres.2017.09.008 2017. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/
Keywords: Dietary patterns; Homocysteine; Long-chain polyunsaturated fatty acids; Methyl donor metabolism; Whole grain